Interview with Sardar Fazlul Kabir, communist turned educationist, on the communist movement of the 1940s and 1950s. Interviewed in Dhaka, 18/11/2007 - Kabir, Shahriar.
Interview with Sardar Fazlul Kabir, communist turned educationist, on the communist movement of the 1940s and 1950s. Interviewed in Dhaka, 18/11/2007.